Frontal fibrosing alopecia: a case series of 65 patients seen in a single Italian centre. (13th December 2018) - Starace, M.; Brandi, N.; Alessandrini, A.; Bruni, F.; Piraccini, B.M.
Abstract: Background: Frontal fibrosing alopecia (FFA) is increasing in prevalence worldwide and several series from different countries have been published, in order to detect possible causes of the disease outbreak. Objective: To analyze the epidemiological, clinical and trichoscopic features of FFA seen in an Italian Dermatology Unit. Methods: Clinical, trichoscopy, histopathology and medical details of all patients were compared with literature and general population data. Results: From 2005 to 2017, we diagnosed FFA in 65 Caucasian females, with the number of diagnoses per year progressively rising. Premenopausal onset was detected in 21%. Frontal hair line recession was associated with parietal involvement in 80% of cases, occipital in 12.3% and eyebrows alopecia in 86.1%. In six cases, eyebrow alopecia preceded hair loss. Non‐inflammatory facial papules were detected in 1/3 of the patients. Itching was reported by 2/3 of the patients and was indicative of disease progression. Trichoscopy showed empty follicles/yellow dots, absence of follicular ostia, mild follicular hyperkeratosis, perifollicular erythema and 'lonely hair'. Scalp lichen plano‐pilaris was seen in 15 patients, female pattern hair loss in 22. Therapy included short‐term treatment with systemic or intralesional corticosteroids followed by therapy with 5α‐reductase inhibitors of hydroxychloroquine and topical drugs. Arrest of FFA progression was seen in 75% of the patients, while 16 experienced worsening of the hairline despite therapy. Conclusions: Frontal fibrosing alopecia not rarely starts before menopause, loss of the eyebrows can be the first sign of the disease, about 50% of the patients have other autoimmune conditions, FFA severity is not related to its duration, itching, follicular hyperkeratosis and erythema at trichoscopy are signs of disease progression, 25% of the patients show progression of hairline recession despite therapy.